13.4k views
5 votes
Given that f(x) = 5x - 10 and g(x) = x + 3, find f(g(-1)).

2 Answers

6 votes

Answer:

0

Explanation:

Evaluate g(- 1) then use this result to evaluate f(x)

g(- 1) = - 1 + 3 = 2, then

f(2) = (5 × 2) - 10 = 10 - 10 = 0

User Avivr
by
5.2k points
2 votes


\bf \begin{cases} f(x) = 5x-10\\ g(x) = x + 3 \end{cases} \\\\[-0.35em] ~\dotfill\\\\ g(-1)=(-1)+3\implies \boxed{g(-1) = 2} \\\\\\ f(~~g(-1)~~)\implies f\left( \boxed{2} \right) = 5(2)-10\implies \stackrel{f(~g(-1)~)}{f(2)}=0

User Matszwecja
by
4.9k points